CD81 is required for rhoptry discharge during host cell invasion by Plasmodium yoelii sporozoites. (2nd June 2014) - Risco‐Castillo, Veronica; Topçu, Selma; Son, Olivia; Briquet, Sylvie; Manzoni, Giulia; Silvie, Olivier
Summary P lasmodium sporozoites are transmitted by Anopheles mosquitoes and first infect the liver of their mammalian host, where they develop as liver stages before the onset of erythrocytic infection and malaria symptoms. Sporozoite entry into hepatocytes is an attractive target for anti‐malarial prophylactic strategies but remains poorly understood at the molecular level. Apicomplexan parasites invade host cells by forming a parasitophorous vacuole that is essential for parasite development, a process that involves secretion of apical organelles called rhoptries. We previously reported that the host membrane protein CD81 is required for infection by Plasmodium falciparum and Plasmodium yoelii sporozoites. CD81 acts at an early stage of infection, possibly at the entry step, but the mechanisms involved are still unknown. To investigate the role of CD81 during sporozoite entry, we generated transgenic P. yoelii parasites expressing fluorescent versions of three known rhoptry proteins, RON2, RON4 and RAP2/3. We observed that RON2 and RON4 are lost following rhoptry discharge during merozoite and sporozoite entry. In contrast, our data indicate that RAP2/3 is secreted into the parasitophorous vacuole during infection. We further show that sporozoite rhoptry discharge occurs only in the presence of CD81, providing the first direct evidence for a role of CD81 during sporozoite productive invasion.